in Vitro Evaluation of Some Known Bioagents to Control Colletotrichum Gloeosporioides Penz. and Sacc., CAUSING Anthracnose of Indian Bean - A.J. DESHMUKH; B.P. MEHTA; V.A.PATIL (International Journal of Pharma and Bio Sciences, 2010)
Investigation on anthracnose (Colletotrichum gloeosporioides Penz. and Sacc.) of Indian bean (Lablab purpureus L) under south Gujarat conditions was carried out in the Plant Pathology Lab., Deptt. of Plant Pathology, N. M. College of Agriculture, Navsari Agricultural University, Navsari during the year 2008-09 to find out suitable management strategies. Due to hazardous effect of chemical fungicides, search for safer alternative to control the pathogen is better choice. This led to trials on the use of bioagents to control the pathogen. The bioagents such as Trichoderma viride,Trichoderma harzianum, Trichoderma longibrachyatum, Gliocladium virens, Chaetomium globosum, Pseudomonas fluorescens, Aspergillus niger, and Bacillus subtilis were evaluated by dual culture, pathogen at periphery and pathogen at the centre technique respectively to monitor antagonistic effect. The results revealed that out of all the eight bioagents used, three bioagents in the three techniques respectively were able to inhibit the growth of the pathogen mycelia significantly, T. viride by (60.69, 58.57, 63.83), T. harzianum by (58.12, 52.27, 58.87) and A. niger by (55.56, 50.46, 57.44) per cent.